Impact of deprivation on hospital efficiency and financial balance in paediatrics. (13th November 2019) - Michel, M; Alberti, C; Carel, J C; Chevrel, K
Abstract: Background: In healthcare systems where hospital tariffs are based on average national length of stay (LOS), deprived patients may be a source of inefficiency for hospitals as deprivation has been shown to be associated with increased LOS. They may also negatively impact hospitals' financial balance as few hospital payment methods include deprivation. Our objective was to study the impact of deprivation on hospital efficiency and financial balance. Methods: A study was carried out using an exhaustive national hospital discharge database. All inpatient stays in mainland France between 2012 and 2014 by children over 28 days and under 18 in hospitals with a paediatric ward were included. Deprivation was estimated with an ecological deprivation index divided into national quintiles. Efficiency was assessed by variations in patients' LOS compared to different mean national LOS (paediatric LOS, LOS of admissions for a similar condition...). Financial balance was assessed at the admission level through the ratio of production costs and revenues and at the hospital level with the difference between all revenues and production costs for said hospital. Multivariate models assessed the association between those indicators and deprivation. Results: 4, 124, 510 inpatient stays were included. LOS was shorter than national means for less deprived patients and longer for the more deprived, and the difference was higher for diagnosis-related groups (DRGs) that included both adult and paediatric patients compared to paediatric-only DRGs. The multivariate model confirmed those significant associations. Deprivation also had a significant impact on hospitals' financial balance, especially for hospitals with a percentage of paediatric patients in the two most deprived quintiles between 20% and 60%. Conclusions: Measures to reform hospital payment methods must be encouraged to improve resource allocation efficiency and equity in access to good paediatric care. Key messages: A reform of hospital funding to better account for deprivation is needed. A modulation of tariffs using an allocation key at the patient level must be considered to mitigate the effect of deprivation. DRGs specific to children should be encouraged to become the norm rather the exception to provide an adequate picture of resources used during admission and therefore an appropriate tariff.